ARTEFAK PERUNGGU PRASEJARAH SITUS PASIR ANGIN BOGOR: HUBUNGANNYA DENGAN ASPEK SUMBER BAHAN - Prijono, Sudarti (BRIN, 2016)
Pasir Angin site is located in the western part of Java Island kept many artifacts coming from metal materials bronze. Bronze at the site was found in context as a means or equipment worship ancestral spirits. The context also shows that Bronze at the time it was considered a luxury item, and community allegedly Pasir Angin was first exposed to goods of metal materials that are the result of high technology. On this site can not be found the remains of bronze production, so it alleged that no local production of bronze artifacts, but to come from surplus areas such objects and how spreading. Through metallographic analysis showed that bronze objects Pasir Angin site making techniques have similarities with the Dong Son bronze objects. In addition, there were traces of shipping and commercial activities that have ever taken place between the Chinese in this case with Indonesia Dong Son bronze objects strengthens the case originated from the region. Thus the site became Pasir Angin setrategis region that gave birth to early civilizations utilization of high technology. The findings of bronze objects on this site strengthens the case that Java has entered International network since the perundagian.